Uji Aktivitas Antioksidan Ekstrak Etanol 70% Daun Pandan Wangi (Pandanus amaryllifolius Roxb) Dengan Metode DPPH - Muhammad Arif; Ayu Rahmawati; Noveri Rahmawati; Nursyafni; Indah, Indah Kurniawati (LPPM, Universitas Muhammadiyah Riau, 2024)
Antioxidants and free radicals are topics that are increasingly discussed in the field of health and lifestyle. Free radicals, which result from oxidative stress, are known to play a role in the development of many serious diseases, such as cancer, cardiovascular disorders and premature aging. Antioxidants are able to neutralize free radicals, thus having the potential to prevent or reduce the impact of these diseases. This study aims to evaluate the antioxidant activity of ethanol extract of pandan wangi leaves (Pandanus amaryllifolius Roxb) using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method and determine the IC50 value as an indicator of effectiveness. Experimental methods were used to analyze antioxidant activity, with DPPH assays performed using a UV-Vis spectrophotometer. The results showed that the ethanol extract of pandan leaves had an IC50 value of 180.21 µg/mL, which was slightly lower than vitamin C as a positive control with an IC50 value of 136.03 µg/mL. Nevertheless, the antioxidant activity of pandan leaf extract is still in the moderate category, indicating its potential as a source of natural antioxidants. This study also emphasizes the importance of technical factors, such as temperature, incubation duration, and solvent quality, in influencing the test results. This study opens up opportunities for further development in the optimization of extraction and utilization of pandan wangi leaves as a natural ingredient to fight oxidative stress.